The Struggles of the Kretek Workers in Iksaka Banu’s Novel, Sang Raja (The King) - Thera Widyastuti (k@ta: A Biannual Publication on the Study of Languange and Literature, 2020)
Novel is able to present the development of one character, complex social situations, relationships involving many or few characters, and complicated events that occurred several years ago in detail. Novel The King was written by Iksana Banu, an famous Indonesian author and artist. He published the novel in 2017. The King tell the story about people who work in Kretek Cigarette factory. They have to struggle how to defend the cigarette factory from competition with other factories, and worldwide economic depression. The main character, Philip Gerardus Rechterhand, a Dutch man who borned in Indonesia. Intrinsic (character and setting), and extrinsic (sociology of literature, personality theory, and history) approaches are using to analyze this research. Kretek become part of society life, and many people have economic dependence on the kretek factory.